AGE, YEARS IN MARRIAGE, LEVEL ON PROGRAMME AND STRESS AMONG MARRIED FEMALE SANDWICH UNDERGRADUATES OF EKITI STATE UNIVERSITY, NIGERIA - Ogunsanmi, Joyce Olufunke (European Scientific Journal, ESJ, 2014)
The study investigated the levels of stress experienced by married female sandwich undergraduates in Ekiti State University, Nigeria. Stressors of interest were occupational stress, family responsibility stress, academic activities stress, financial stress, cultural roles stress, religious roles stress and programme generated stress. The influences of age, years in marriage and level on academic programme on stress experiencedamong the women were examined. The study was a descriptive research of the survey type. The population was all married female sandwich undergraduates in four hundred (400) and five hundred (500) levels of 2012/2013 academic session of Ekiti State University, AdoEkiti, Nigeria. A sample of 200 women was selected through stratified random sampling techniques. The research instrument was a questionnaire which was validated by the researcher. One (1) research question was raised and one (3) research hypotheses were postulated and tested at 0.05 level of significance. Results of the analyses revealed that the women experienced different levels of stress.Counselling implications of the findings were highlighted. Based on the findings, it was recommended that young married female should delay participation in the rigorous sandwich programme. Since the years in marriage and level on the programme were significant, interested newly married women should wait for some years into their marriage before embarking on the programme. Also, married female undergraduates should be counseled to develop coping methods to care for their various roles as married women on the programme.